Do Votes Speak Louder than Motives? Moral Judgments and Tolerance in the 2016 Presidential Election. Issue 1 (12th March 2018) - Huff, Sarah T.; Hall, Michael P.
Abstract: When judging a voter's decision, does that voter's reason for casting their vote influence moral and interpersonal judgments about them? In the context of the 2016 U.S. Presidential Election, past research suggests two competing predictions. First, people regularly account for an actor's intentions when forming judgments of the actor, indicating that judgments may vary according to a voter's motives. However, people are unlikely to see nuance among outgroups, especially amid divisive political partisanship, suggesting that judgments would ignore information about voters' motives. In Study 1, results supported the first prediction, showing that both Hillary Clinton and Donald Trump supporters distinguished between different voting motives when making moral and interpersonal judgments of outgroup voters. In Studies 2 and 3, when some voters' motives became more extreme, Clinton and Trump supporters again distinguished between voting motives for outgroup and ingroup voters, respectively, albeit in a different pattern of results.